Store-Operated Ca(2+) Entry (SOCE) and Purinergic Receptor-Mediated Ca(2+) Homeostasis in Murine bv2 Microglia Cells: Early Cellular Responses to ATP-Mediated Microglia Activation. - Gilbert, Daniel; Stebbing, Martin J.; Künzel, Katharina; Murphy, Robyn M.; Zacharewicz, Evelyn; Buttgereit, Andreas; Stokes, Leanne; Adams, David J.; Friedrich, Oliver (Frontiers in Molecular Neuroscience, 2016)
Microglia activation is a neuroinflammatory response to parenchymal damage with release of intracellular metabolites, e.g., purines, and signaling molecules from damaged cells. Extracellular purines can elicit Ca(2+)-mediated microglia activation involving P2X/P2Y receptors with metabotropic (P2Y) and ionotropic (P2X) cell signaling in target cells. Such microglia activation results in increased phagocytic activity, activation of their inflammasome and release of cytokines to sustain neuroinflammatory (so-called M1/M2 polarization). ATP-induced activation of ionotropic P2X4 and P2X7 receptors differentially induces receptor-operated Ca(2+) entry (ROCE). Although store-operated Ca(2+) entry (SOCE) was identified to modulate ROCE in primary microglia, its existence and role in one of the most common murine microglia cell line, BV2, is unknown. To dissect SOCE from ROCE in BV2 cells, we applied high-resolution multiphoton Ca(2+) imaging. After depleting internal Ca(2+) stores, SOCE was clearly detectable. High ATP concentrations (1 mM) elicited sustained increases in intracellular [Ca(2+)]i whereas lower concentrations (≤100 μM) also induced Ca(2+) oscillations. These differential responses were assigned to P2X7 and P2X4 activation, respectively. Pharmacologically inhibiting P2Y and P2X responses did not affect SOCE, and in fact, P2Y-responses were barely detectable in BV2 cells. STIM1S content was significantly upregulated by 1 mM ATP. As P2X-mediated Ca(2+) oscillations were rare events in single cells, we implemented a high-content screening approach that allows to record Ca(2+) signal patterns from a large number of individual cells at lower optical resolution. Using automated classifier analysis, several drugs (minocycline, U73122, U73343, wortmannin, LY294002, AZ10606120) were tested on their profile to act on Ca(2+) oscillations (P2X4) and sustained [Ca(2+)]i increases. We demonstrate specific drug effects on purinergic Ca(2+) pathways and provide new pharmacological insights into Ca(2+) oscillations in BV2 cells. For example, minocycline inhibits both P2X7- and P2X4-mediated Ca(2+)-responses, and this may explain its anti-inflammatory action in neuroinflammatory disease. As a technical result, our novel automated bio-screening approach provides a biomedical engineering platform to allow high-content drug library screens to study neuro-inflammation in vitro.